(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper assesses the impact of initiatives introduced by the Modi government aimed at enhancing food security, improving nutrition outcomes, and promoting agricultural development in India. Key policies examined include the National Nutrition Mission (Poshan Abhiyan), the National Food Security Act (NFSA), and the Food Fortification Initiative. These initiatives target challenges of malnutrition among vulnerable groups and strive to ensure food availability and accessibility through subsidized grains and fortified staple foods. Additionally, the study investigates the Pradhan Mantri Kisan Samman Nidhi (PM-KISAN) scheme, which provides support to small and marginal farmers, potentially influencing agricultural practices and production. The research also considers the government’s increased investment in agricultural research and development, highlighting its indirect contributions to food production, quality improvement, and nutritional enhancement. Through an analysis of these initiatives, this paper offers insights into their effectiveness, challenges faced during implementation, and implications for future policy directions in the realms of food security, nutrition, and agricultural development in India under the Modi administration.